Model Penguatan Kelembagaan Lokal dalam Penanggulangan Kemiskinan di Wilayah Perbatasan RI-DTL - Dominikus Mau Bele; Sanggar Kanto; Edi Susilo (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2021)
The RI-RDTL border became an area of conflict between the communities in Makir Village and Lamaksenulu Village. This conflict often results in several criminal acts such as burglary, theft of livestock, confiscation of water to rice fields. Coupled with low physical development conditions, for example, the unavailability of clean water and heavily damaged road access, increase the poverty rate. This conflict factor is also caused by the lack of attention from the government, both in terms of education. Through this case study, the social reality of the border conflict in the RI-RDTL Border Region of the Belu Regency will be revealed. By using the theory of democracy as a theoretical framework, the purpose of this study is to propose a model for strengthening local institutions in disaster management. Data collection techniques used in this study include observation, interviews, and documentation. Focus Group Discussions (FGD) using technical comparison data were also conducted to increase the validity of the data obtained. The findings of this study are in the form of a model for strengthening local indigenous peoples' institutions in the form of Ti'sian Tak Ni'an in Makir and Lamaksenulu Villages. This model is expected to create a sense of togetherness, mutual cooperation, and community participation in sustainable development planning. Empowerment and capacity building of these communities can encourage them to lead a better and more prosperous life.